Knowledge, attitude and practicing behaviour regarding antimicrobial use and awareness of antimicrobial resistance among clinicians - Nishat, Samreen; Jalal, Javeria; Butul, Maleha; Akhter, Syeda Neha; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2022)
Background: Antimicrobials' irrational use is leading to antimicrobial resistance. This situation has become a public health care issue and must be tackled by clinicians. The awareness about antimicrobial resistance and proper usage by patients must be looked after by clinicians. Hence, the present study was taken to determine the knowledge, attitude, and practicing behaviour regarding antimicrobial use and awareness of antimicrobial resistance among clinicians. Methods: The study was conducted on clinicians in a tertiary care hospital. A standardized questionnaire was distributed to 110 participants and ethical approval was taken before the study. Data was analyzed using SPSS software. For data comparisons, chi-square tests were used. P≤0.05*, considered significant. Results: The study showed a majority in the 25-34 years of age group with male predominance. Many belonged to the 1-0 years of practicing group and the majority were physicians. The antibiotic resistance subject was highly relevant to clinicians, according to them awareness can be spread by proper and precise intake of antibiotics by patients. The relationship between the predominant age group and years of practice revealed good knowledge (χ2=56.703, p=0.01), fair attitude (χ2=69.556, p=0.01), and good practicing behavior (χ2=43.047, p=0.01). Conclusions: Clinicians were aware of antimicrobial resistance issue globally but irrelevant in their own practice. Patient awareness campaigns and educational programs need to be conducted. Lack of time and patient interest are the barriers to be overcome to spread awareness. The prescribing of antimicrobials should be in a controlled way with the implementation of ethical principles for better patients' health safety.